Meaning in life as a mediator between interpersonal alienation and smartphone addiction in the context of Covid-19: A three-wave longitudinal study. (February 2022) - Hu, Qiong; Liu, Qinxue; Wang, Zongyuan
Abstract: In the context of the Covid-19, the present study designed a longitudinal study to examine the relationship among interpersonal alienation, meaning in life and smartphone addiction. Meanwhile, with the development of the epidemic whether there would be changes in the three variables was also examined. A sample of 579 university students (baseline mean age = 20.59, SD = 2.20) finished the anonymous questionnaires about interpersonal alienation, meaning in life and smartphone addiction. Three repeated measurements were obtained in June, September and December 2020. The finding indicated that university students' interpersonal alienation and meaning in life significantly increased, and the risk of smartphone addiction significantly decreased with the epidemic under control. Besides, meaning in life in the middle mitigating period of the epidemic mediated the relationship between interpersonal alienation in the early severe period of the epidemic and smartphone addiction in the basic end period of the epidemic. The study contributes to our understanding of how low levels of interpersonal alienation may improve meaning in life and reduce the risk of smartphone addiction. What' s more, it provides scientific suggestions for the prevention and intervention of the adverse effects during public health emergencies. Highlights: Interpersonal alienation and meaning in life increased with the epidemic under control. The risk of smartphone addiction decreased with the epidemic under control. Interpersonal alienation negatively predicted subsequent meaning in life. Interpersonal alienation positively predicted subsequent smartphone addiction. Meaning in life had indirect effects on interpersonal alienation and smartphone addiction.